Economy-wide implications of increasing school enrolment in Sub-Saharan Africa - Elnour, Zuhal; Siddig, Khalid; Grethe, Harald (Elsevier, 2025)
The high number of out-of-school youth in developing countries constitutes a pressing challenge with profound implications for attaining sustainable development. Sudan, for example, has the fifth-highest number globally while struggling with sluggish economic growth and high youth unemployment. In this study, we assess the potential economy-wide implications of options to enhance enrolment among youth by lowering private household spending on education and training services, taking Sudan as a case study. Cost reduction is considered for: a) primary education, b) secondary education, c) primary and secondary education, and d) all formal educational cycles and vocational training. We developed a recursive-dynamic single-country Computable General Equilibrium (STAGE-Edu) model that captures vocational training, secondary education by type (vocational and non-vocational), and education and training choices at different levels, with broad coverage of existing bridges between education and training. STAGE-Edu also establishes endogenous and consistent linkages between the educational and training system and the skill levels of the labour force through six-stage nested production functions. The findings suggest that cost reduction in primary education significantly reduces the number of out-of-school children and enhances long-term economic growth. However, it increases dropouts from post-primary education and vocational training. In contrast, cost reduction for both primary and secondary education improves enrolment in the tertiary education cycle and promotes the overall skill composition. Funding such cost reductions from foreign development aid and grants yields higher economic benefits than increasing domestic taxes.